PENERAPAN PRINSIP KEADILAN RESTORATIF DALAM PENYIDIKAN TINDAK PIDANA PENGANIAYAAN YANG DILAKUKAN OLEH ANAK PADA PONDOK PESANTREN NURUL IKHLAS (Studi Kasus Pada Unit PPA Polres Padang Panjang) - Cepi Noval (UNES Law Review, 2022)
The obligation of restorative justice in children's cases is a necessity for investigators. This is confirmed in Article 5 of the SPPA Law. However, in its implementation it encountered challenges, especially at the investigation level, such as the case of the persecution that occurred at the Nurul Ikhlas Islamic Boarding School as reported by the police report LP/05/II/SPKT II/2019/Sek X Koto. In order to realize restorative action, investigators received a confession from the victim's family. Although the application of the principle of restorative justice is a must for law enforcement in the interests of children, it cannot be denied that there are still weaknesses in its implementation. The application of the principle of restorative justice in the investigation of criminal acts in the police report number LP/05/II/SPKT II/2019/Sek X Koto, investigators apply the principle of restorative justice to the investigation by involving the TP2TPA for legal services. Furthermore, at the investigation stage, they did not detain the perpetrator and approached the victim's family to accept the offer from the child perpetrator even though he received a reply. Obstacles in applying restorative justice at the investigation level consist of juridical constraints, namely: the application of the principles of restorative justice through the diversion model and cannot be applied to all criminal acts, depending on the threat of criminal and not criminal acts and there is a written agreement from the reporting party. Non-juridical constraints are that investigators have not acted as mediators at the time of the dialogue between the parties and the view of restorative justice by the community and the culture that punishment is retaliation for perpetrators of criminal acts is still attached.